2022
DOI: 10.18494/sam.2021.3448
|View full text |Cite
|
Sign up to set email alerts
|

In situ Visualization of Ferrous Ions Dissolved from Pure Iron Wire into Thin Frozen Aqueous Solution Films by Combination of Microscopy and Image Processing

Abstract: The dissolution of ferrous ions from pure iron into freeze-concentrated solutions (FCSs) formed in thin films of aqueous salt solutions was visualized by a combination of in situ diffusive-reflection microscopy and image processing. An iron surface in contact with an FCS was observed with a diffusive-reflection microscope. Ferrous ions dissolved from the iron surface were complexed with 1,10-phenanthroline doped in the ice film to develop reddish complexes. In situ observation enabled us to monitor the dissolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…To overcome this issue, our research group has reported a microscopic method for the evaluation of ferrous iron from pure iron wire dissolved in an FCS. 12) The ferrous ions dissolved from the wire were complexed with 1,10-phenanthroline doped in the FCS, and the resulting coloration was observed employing microscopy, followed by quantitative evaluation using an image processing tool. We successfully visualized the dissolution behavior of the ferrous ions in the FCS.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this issue, our research group has reported a microscopic method for the evaluation of ferrous iron from pure iron wire dissolved in an FCS. 12) The ferrous ions dissolved from the wire were complexed with 1,10-phenanthroline doped in the FCS, and the resulting coloration was observed employing microscopy, followed by quantitative evaluation using an image processing tool. We successfully visualized the dissolution behavior of the ferrous ions in the FCS.…”
Section: Introductionmentioning
confidence: 99%